2009
DOI: 10.1074/jbc.m807307200
|View full text |Cite
|
Sign up to set email alerts
|

GATA Transcription Factors Regulate the Expression of the Human Eosinophil-derived Neurotoxin (RNase 2) Gene

Abstract: The transcription factors GATA-1 and GATA-2 have been implicated in promoting differentiation of eosinophilic leukocytes. In this study, we examined the roles of GATA-1 and GATA-2 in activating transcription of the secretory ribonuclease, the eosinophil-derived neurotoxin (EDN/RNase 2). Augmented expression of both GATA-1 and GATA-2 was detected in eosinophil promyelocyte HL-60 clone 15 cells in response to biochemical differentiation with butyric acid. Deletion or mutation of one or both of the two consensus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 46 publications
2
29
0
Order By: Relevance
“…These results thus demonstrate that G1-GFP is a useful marker for eosinophil isolation from the bone marrow, and that cells in the eosinophil lineage are highly enriched in the G1-R1 fraction. It is interesting to note that, in agreement with previous reports on eosinophils (Querfurth et al 2000;McNagny and Graf 2002;Qiu et al 2009), both Gata1 and Gata2 mRNA was expressed in the G1-R1 eosinophilic fraction.…”
Section: Genesupporting
confidence: 75%
See 3 more Smart Citations
“…These results thus demonstrate that G1-GFP is a useful marker for eosinophil isolation from the bone marrow, and that cells in the eosinophil lineage are highly enriched in the G1-R1 fraction. It is interesting to note that, in agreement with previous reports on eosinophils (Querfurth et al 2000;McNagny and Graf 2002;Qiu et al 2009), both Gata1 and Gata2 mRNA was expressed in the G1-R1 eosinophilic fraction.…”
Section: Genesupporting
confidence: 75%
“…3A) in LyE -/c-Kit -/CD71 -bone marrow cells. In addition, several reports have demonstrated simultaneous expression of the Gata1 and Gata2 genes in EoP fractionated with an anti-IL-5Rα antibody from mouse bone marrow (Iwasaki et al 2005(Iwasaki et al , 2006Mori et al 2009) or in eosinophils obtained by culturing progenitor cells (Qiu et al 2009). However, the major eosinophilic fraction in G1-Red:G2-GFP mouse bone marrow is the G1-Red + /G2-GFP -(G1G2-R3) fraction, in which the Gata2 mRNA expression level is very low or undetectable by quantitative RT-PCR analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GATA-1 is expressed in human peripheral eosinophils and eosinophilic cell lines (24), and eosinophil progenitors are found exclusively within cells activating GATA-1 transcription (25). The promoters of the genes that encode the eosinophil-specific major basic proteins (MBPs), Charcot-Leyden crystal protein and eosinophil-derived neurotoxin (EDN), contain functional GATA elements at which GATA-1 interacts with other transcription factors to activate transcription (26)(27)(28). Zimmermann et al (19) showed that GATA-1 binds to a double-GATA element within exon 1 of the CCR3 gene.…”
mentioning
confidence: 99%